Radiation resistance of near-infrared photodiodes based on Hg3In2Te6 - Skliarchuk, Valerii; Fochuk, Petro; Bolotnikov, A.; James, Ralf (SPIE, 2021)
The design and technology for manufacturing of photodiodes with a potential barrier created by a Schottky contact on a substrate of radiation-resistant n-Hg3In2Te6 single crystal are presented. The photosensitivity of the photodetector covers the wavelength range ≈0.6-1.6 μm at the maximum current monochromatic sensitivity S≈1.15 A/wt for max≈1.55 μm. To study the effect of the contact material on the effect of the absorbed dose of ionizing radiation, two types of photodetectors Ni/n-Hg3In2Te6/In and Cr/n-Hg3In2Te6/Cr were fabricated. A study of the effect of absorbed doses of ionizing radiation D1105 , D2106 і D3107 Gray on the main parameters of photodetectors (i.e., S, max, dark currents at forward and reverse bias, open circuit voltage, and short circuit current). Photodiodes, based on mercury-indium telluride (HgInTe), showed a high resistance to ionizing radiation. The best resistance to ionizing radiation was shown by Cr/HgInTe/Cr photodiodes, which slightly changed their basic parameters at the absorbed dose of D3107 Gray. The Ni/HgInTe/In photodetectors lost their function after exposure to an absorbed dose of D3107 Gray. In Ni/HgInTe/In photodetectors the absorbed dose of D3107 Gray practically destroyed the indium contact. 30-50 % of the nickel front contact was also destroyed. For comparison, similar studies were performed with photodetectors based on cadmium telluride Cr/CdTe/In prepared by the authors an well as silicon. The silicon-based photodetectors used in this study were provided by industrial sources.
Keywords: photodetector with potential Schottky barrier; radiation resistance; Hg3In2Te6; Cr